Analysis of Factors Influencing the Consumption of Fish in Indonesian Women - Nurjanah Nurjanah; Taufik Hidayat; Silvia Mawarti Perdana (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2015)
This study aimed to analyze factors affected fish consumption of Indonesian women. This research design was a cross-sectional referred to the Basic Health Research in 2010, conducted by the Health Institute for Research and Development The Ministry of Health Republic of Indonesia. Objects of this study were women within 19-55 years old. The variabel such as nutritional status, social economy and fish consumption were analysed using logistic regression method. The analysis showed that the consumption of fish protein accounted for 19.1 g/day or 82% of total animal protein intake in women subjected in this research, however thisconsumption only met 34% requirement of protein per day. The average of body mass index of the women was 23.2 ± 4.0 kg/m2 and was categorized as normal nutritional status. Positive relationship was found between fish consumption, intake of fat, and nutritional status. The consumption of fish was affected by marital status and economic status. Women with marital status had 1.13 times higher likelihood to consume fish than unmarried women. Economic status also determined fish consumption volume.